Profil Gambaran Histopatologi Hepar Tikus Putih (Rattus norvegicus) Betina Galur Sprague Dawley yang Terpajan 7,12 Dimetilbenz(α)Antracene dan Diberi Ekstrak Etanol Umbi Bawang Dayak (Eleutherine bulbosa (Mill.) Urb.) - Jonathan Edgar (Majalah Kedokteran Andalas, 2022)
AbstractObjective : The purpose of this study is to describe the histopathological profile of the liver in Sprague Dawley white rats exposed to DMBA and given ethanol extract of bawang dayak bulbs (EEUBD). Methods : The method used in this research is descriptive by comparing the profile of 5 groups of white female rats  Sprague Dawley strain. Each group comprised of five rats. Group I (DMBA control group) received DMBA at a dosage of 20 mg/kgBW, while Normal group was given corn oil and DMSO 5% only. The other three groups received DMBA + EEUBD at dosages of 180 mg/kgBW, 360 mg/kgBW, and 720 mg/kgBW. At the end of the study, rat livers were collected and stained with hematoxylin and eosin (H&E) Results : The results obtained by the Kruskal-Wallis test showed a p value of 0.512 for the difference in the mean results of each treatment group. Conclusion : There was no significant difference between the three treatment doses on the histopathological liver profile of white rats induced by DMBA . Keywords: Eleutherine bulbosa; Histopathology; Liver; DMBA; White rat